Hepatitis B virus reactivation in a myeloma patient with resolved infection who received daratumumab-containing salvage chemotherapy - Kikuchi, Takaki (J Clin Exp Hematop, 2020)
A 72-year-old female complaining of back pain was diagnosed with IgG-κ multiple myeloma. After osteosynthesis for fracture of the left femoral shaft due to myeloma, she received bortezomib, melphalan, and prednisolone as an initial regimen for multiple myeloma, but discontinued it after three courses due to progressive disease. The patient subsequently received lenalidomide and dexamethasone as a second-line regimen for 2.5 years, and pomalidomide and dexamethasone as a third-line regimen for only 2 months. An anti-CD38 monoclonal antibody, daratumumab (DARA), and bortezomib and dexamethasone (DVd) as a fourth-line regimen were administered for refractory myeloma. However, hepatitis B virus (HBV) reactivation occurred on day 15 of the third course of DVd. The HBV DNA level in peripheral blood suddenly increased to 2.2 log IU/mL. An anti-HBV nucleotide analog, entecavir, was subsequently administered when the HBV DNA level increased to 2.6 log IU/mL. No HBV-related hepatitis was observed during follow-up. DARA can improve the prognosis of patients with multiple myeloma, but also potentially increase the risk of HBV reactivation. Host and viral risk factors need to be identified in such patients in order to implement a more cost-effective strategy against HBV reactivation.